The Influence of Price, Marketing Strategy, and Creativity on Purchase Decisions at PT. Terbit Terang Medan - Cindy Eka Rivanni; Andi Susanto Zamili; Debora Intan Yosephine; Rosinta Romauli Situmeang (Kontigensi : Jurnal Ilmiah Manajemen, 2021)
This study aims to determine the effect of price, marketing strategy, and creativity on purchasing decisions at PT. Terbit Terang Medan. Data collection using a questionnaire, multiple linear regression analysis models. The study results show that price, marketing strategy, and creativity affect purchasing decisions at PT. Terbit Terang Medan with a coefficient of determination R square 0.547. Price partially influences purchasing decisions with a coefficient value of 0.710; Marketing Strategy partially affects 0.038, creativity partially affects purchasing decisions with a coefficient value of 0.282, The dominant factor influencing purchasing decisions is price.